Continuous-flow Heck synthesis of 4-methoxybiphenyl and methyl 4-methoxycinnamate in supercritical carbon dioxide expanded solvent solutions - Lau, Phei Li; Allen, Ray W. K.; Styring, Peter (Beilstein Journal of Organic Chemistry, 2013)
The palladium metal catalysed Heck reaction of 4-iodoanisole with styrene or methyl acrylate has been studied in a continuous plug flow reactor (PFR) using supercritical carbon dioxide (scCO2) as the solvent, with THF and methanol as modifiers. The catalyst was 2% palladium on silica and the base was diisopropylethylamine due to its solubility in the reaction solvent. No phosphine co-catalysts were used so the work-up procedure was simplified and the green credentials of the reaction were enhanced. The reactions were studied as a function of temperature, pressure and flow rate and in the case of the reaction with styrene compared against a standard, stirred autoclave reaction. Conversion was determined and, in the case of the reaction with styrene, the isomeric product distribution was monitored by GC. In the case of the reaction with methyl acrylate the reactor was scaled from a 1.0 mm to 3.9 mm internal diameter and the conversion and turnover frequency determined. The results show that the Heck reaction can be effectively performed in scCO2 under continuous flow conditions with a palladium metal, phosphine-free catalyst, but care must be taken when selecting the reaction temperature in order to ensure the appropriate isomer distribution is achieved. Higher reaction temperatures were found to enhance formation of the branched terminal alkene isomer as opposed to the linear trans-isomer.
Keywords: continuous flow; flow chemistry; Heck; palladium; supercritical carbon dioxide

(untitled) - de Meijere, A.; Bräse, S. (J. Organomet. Chem., 1999)

(untitled) - Heck, R. F.; Nolley, J. P., Jr (J. Org. Chem., 1972)

(untitled) - Phan, N. T. S.; Brown, D. H.; Adams, H.; Spey, S. E.; Styring, P. (Dalton Trans., 2004)

(untitled) - Phan, N. T. S.; Brown, D. H.; Styring, P. (Tetrahedron Lett., 2004)

(untitled) - Phan, N. T. S.; Brown, D. H.; Styring, P. (Green Chem., 2004)

Metal-Catalysed Cross-Coupling Reactions - Diederich, F.; Stang, P. J. (Wiley-VCH, 1998)

(untitled) - Köhler, K.; Heidenreich, R. G.; Krauter, J. G. E.; Pietsch, M. (Chem.–Eur. J., 2002)

(untitled) - Bhanage, B. M.; Zhao, F.-G.; Shirai, M.; Arai, M. (Tetrahedron Lett., 1998)

Green Reaction Media in Organic Synthesis - Mikami, K. (Blackwell Publishing, 2005)

Chemical Synthesis Using Supercritical Fluids - Jessop, P. G.; Leitner, W. (Wiley-VCH, 1999)

(untitled) - Leitner, W. (Acc. Chem. Res., 2002)

(untitled) - Raynor, C. M. (Org. Process Res. Dev., 2007)

(untitled) - Carroll, M. A.; Holmes, A. B. (Chem. Commun., 1998)

(untitled) - Morita, D. K.; Pesiri, D. R.; David, S. A.; Glaze, W. H.; Tumas, W. (Chem. Commun., 1998)

(untitled) - Styring, P.; Grindon, C.; Fisher, C. M. (Catal. Lett., 2001)

(untitled) - Alonso, F.; Beletskaya, I. P.; Yus, M. (Tetrahedron, 2005)

(untitled) - Kohler, K.; Prockl, S. S.; Kleist, W. (Curr. Org. Chem., 2006)

(untitled) - Zhao, F.; Shirai, M.; Ikushima, Y.; Arai, M. (J. Mol. Catal. A: Chem., 2002)

(untitled) - Horniakova, J.; Raja, T.; Kubota, Y.; Sugi, Y. (J. Mol. Catal. A: Chem., 2004)

(untitled) - Corma, A.; García, H.; Leyva, A. (Tetrahedron, 2004)

(untitled) - Tsai, F.-Y.; Wu, C.-L.; Mou, C.-Y.; Chao, M.-C.; Lin, H.-P.; Liu, S.-T. (Tetrahedron Lett., 2004)

(untitled) - Dams, M.; Drijkoningen, L.; De Vos, D.; Jacobs, P. (Chem. Commun., 2002)

(untitled) - Corma, A.; García, H.; Leyva, A.; Primo, A. (Appl. Catal., A, 2003)

(untitled) - Poyatos, M.; Márquez, F.; Peris, E.; Claver, C.; Fernandez, E. (New J. Chem., 2003)

(untitled) - Choudary, B. M.; Madhi, S.; Chowdari, N. S.; Kantam, M. L.; Sreedhar, B. (J. Am. Chem. Soc., 2002)

(untitled) - Karbass, N.; Sans, V.; Garcia-Verdugo, E.; Burguete, M. I.; Luis, S. V. (Chem. Commun., 2006)

(untitled) - Phan, N. T. S.; Khan, J.; Styring, P. (Tetrahedron, 2005)

Polymer-Supported Catalysts for Greener Synthesis - Phan, N. T. S. (The University of Sheffield, 2005)

(untitled) - Lee, C. K. Y.; Holmes, A. B.; Ley, S. V.; McConvey, I. F.; Al-Duri, B.; Leeke, G. A.; Santos, R. C. D.; Seville, J. P. K. (Chem. Commun., 2005)

(untitled) - Liu, S.; Fukuyama, T.; Sato, M.; Ryu, I. (Org. Process Res. Dev., 2004)

(untitled) - Solodenko, W.; Wen, H.; Leue, S.; Stuhlmann, F.; Sourkouni-Argirusi, G.; Jas, G.; Schönfeld, H.; Kunz, U.; Kirschning, A. (Eur. J. Org. Chem., 2004)

(untitled) - Cwik, A.; Hell, Z.; Figueras, F. (Adv. Synth. Catal., 2006)

(untitled) - Hillier, A. C.; Grasa, G. A.; Viciu, M. S.; Lee, H. M.; Yang, C.; Nolan, S. P. (J. Organomet. Chem., 2002)

(untitled) - Beletskaya, I. P.; Cheprakov, A. V. (Chem. Rev., 2000)